Features associated with high‐risk sessile serrated polyps at index and follow‐up colonoscopy. Issue 6 (12th November 2020) - Anwar, Shahzaib; Cock, Charles; Young, Joanne; Young, Graeme P; Meng, Rosie; Simpson, Kalindra; Coats, Michelle; Huang, Junming; Bampton, Peter; Fraser, Robert; Symonds, Erin L
Abstract: Background and Aim: Clinically significant serrated polyps are precursors of colorectal cancers, with features considered high risk including size ≥10 mm, dysplasia, and presence of synchronous conventional adenoma. While these features have been described in cohorts undergoing screening colonoscopy, there is little information regarding the prevalence and patient characteristics associated with high‐risk sessile serrated polyps (SSPs) in those undergoing surveillance colonoscopy. Methods: Polyp pathology at the index and first follow‐up colonoscopy performed between 2004 and 2019 were examined in patients enrolled in a surveillance program because of an index finding of adenoma and/or SSP. Demographics and pathology features for SSP were compared between the colonoscopies. Results: Of 6297 patients undergoing index colonoscopy, 2035 underwent follow‐up colonoscopy after 3.3 years (interquartile range 2.1–4.8 years). The proportion with SSP decreased from 7.6% at index to 5.0% at follow‐up ( P < 0.001); however, the proportion of SSPs that were considered high risk was not different between the colonoscopies (62.8% vs 62.4%). Female gender was associated with the presence of high‐risk SSP at index colonoscopy (odds ratio [OR] 1.62, 95% confidence interval [CI] 1.28–2.06), while age ≥75 years (OR 3.38, 95% CI 1.67–6.81) and previous high‐risk SSP (OR 9.40, 95% CI 4.23–20.88) were independently associated with high‐risk SSP at follow‐up. Conclusions: The prevalence of SSP falls by one‐third at first follow‐up colonoscopy although the proportion of SSP with high‐risk features remains the same. While females were more likely to have a high‐risk SSP at the index colonoscopy, those at greatest risk for high‐risk SSP at follow‐up colonoscopy were age >75 years and an index high‐risk SSP.